Implementasi Metode Profile Matching Pada Sistem Pendukung Keputusan Seleksi Calon Ketua OSIS - Amat Damuri; Herry Wahyono; Nuke L Chusna (Journal of Information System Research (JOSH), 2022)
OSIS is the highest organization in the school that functions to mobilize students to be able to contribute to various activities that support the school. To get the OSIS chairperson, it begins with the registration of candidate candidates, then continues with a meeting to determine the candidate for the OSIS chairman. This is considered ineffective because there are no special criteria, so it is not right on target. In addition, the selection process in this way takes a long time. The purpose of this study is to develop a decision support system to select a candidate for the OSIS chairman by using the profile matching method through the required criteria so that the process will be faster and more precise. The profile matching method has the ability to determine the assessment based on the existing attributes. Based on the calculation of profile matching manually and the system built shows the same results. Based on the case study, candidate 1 got a final score of 9.14 and candidate 2 got a final score of 9.215. The results of the assessment of test cases that have been filled in by system users get the system functions developed in accordance with the test criteria carried out. As for the results of black-box testing, the value is 100%, this means that the system is in accordance with the functions and needs.